2019
DOI: 10.1590/1983-21252019v32n130rc
|View full text |Cite
|
Sign up to set email alerts
|

REACTION OF MELON GENOTYPES TO THE ROOT´S ROT CAUSED BY Monosporascus

Abstract: Monosporascus root rot and vine decline (MRRVD) is an important disease in the melon crop in Brazil. In our research, we evaluated the reaction of 45 melon genotypes to M. cannonballus in two successive cropping seasons in a greenhouse. Melon seedlings were transplanted into naturally infested soil. The evaluation of the genotypes was performed after 55 days, using a score scale to group each genotype into one of five classes and to calculate the disease severity index. None of the genotypes showed an immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Another important look of this work is that the species have a different behavior due to accessions. Despite this, it was found that the species M. cannonballus , notoriously the agent of MRRVD worldwide (Sarpeleh 2008; Al-Mawaali et al 2013; Yan et al 2016; Markakis et al 2018; Sales Júnior et al 2019) and the novel species M. mossoroensis was the least virulent since none of the accessions was classified as susceptible to both species. Particularly, the accession A-16 was highly resistant to M. cannonballus , and of moderate or high resistance when inoculated with each of these species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important look of this work is that the species have a different behavior due to accessions. Despite this, it was found that the species M. cannonballus , notoriously the agent of MRRVD worldwide (Sarpeleh 2008; Al-Mawaali et al 2013; Yan et al 2016; Markakis et al 2018; Sales Júnior et al 2019) and the novel species M. mossoroensis was the least virulent since none of the accessions was classified as susceptible to both species. Particularly, the accession A-16 was highly resistant to M. cannonballus , and of moderate or high resistance when inoculated with each of these species.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the following classes of genotypes were separated. 0: like immune; 0.1-1.0: highly resistant; 1.1-2.0: moderately resistant; 2.1-3.0: susceptible; 3.1-4.0: highly susceptible (Sales Júnior et al, 2019). The RI DM was calculated by the following expression: RI DM = (DMc - DMi) / (DMc), where DMc: dry matter of access without inoculation (control) and DMi: matter access inoculated with one of the species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening assays aimed at the identification of tolerance or resistance to collapse caused by M. cannonballus have been carried out in different conditions (Crosby, 2000a;Crosby, Wolff, & Miller, 2000;Esteva & Nuez, 1994;Sales Júnior, Senhor, Michereff, & Negreiros, 2019;Wolff, 1995;Wolff & Miller, 1998). However, very few resistance sources have been identified so far.…”
Section: Field Responsementioning
confidence: 99%
“…However, very few resistance sources have been identified so far. A recent screening of commercial melon cultivars under natural M. cannonballus-infested soils in Brazil has attributed the difficulty in identifying resistant sources to the aggressiveness of the pathogen (Sales Júnior, Senhor, Michereff, & Negreiros, 2019). The influence of the environmental factors in the expression of symptoms has also been reported as hindering the identification of resistance sources (Cohen et al, 2000;Fita, Picó, Monforte, & Nuez, 2008).…”
Section: Field Responsementioning
confidence: 99%